Bistable effect of organic enrichment on sea spray radiative properties. Issue 24 (16th December 2013) - Vaishya, Aditya; Ovadnevaite, Jurgita; Bialek, Jakub; Jennings, S. Gerard; Ceburnis, Darius; O'Dowd, Colin D.
Abstract [1] Primary‐produced sea spray aerosol, typically comprising sea‐salt, but also enriched with organic matter (OM) in biologically active oceanic regions, impacts the global radiative budget through contributions to aerosol optical depth. We show that sea spray light‐scattering enhancement, f(RH), as a function of relative humidity (RH) is suppressed when enriched with OM. A new hygroscopic growth factor parameterization reveals a dual hygroscopicity state, flipping from high hygroscopicity and high f(RH) to low hygroscopicity and low f(RH) as the OM mixing volume percentage exceeds ~ 55% in sea spray. Under elevated wind speeds, this affects the Top‐of‐atmosphere direct radiative forcing (ΔF) by reducing the cooling contribution of sea spray by ~ 5.5 times compared to pure sea‐salt spray. These results suggest a positive feedback coupling between the marine biosphere, sea spray aerosol, and the direct radiative budget.